A study in industrial robot programming - Yusop, Yusmarnita (2004)
This project is concerned with learning the tec1mology and programming of servo controlled industrial robots. A Mitsubishi RV-2AJ articulated robot was used in this project. The project work is divided into two parts: In the first part of the project the author familiarized herself with the operation and programming of the robot's manipulator and controller hardware by carrying out some laboratory experiments. A set oflaboratory sheets were produced from this exercise. In the second part, the author studied the mechanics of software control of the robot. A user-defined trajectory planning routine based on the cubic spline fitting function has successfhlly been developed in this project.